Proposal for teaching-learning body guidance to contribute to the organised attack of football category 13 (Impetus, 2020)
The development of soccer, over the years, has generated that training is increasingly focused on aspects that at first glance do not seem to be decisive in the game. Therefore, it is important to develop motor skills that allow the human being to function optimally in any sports context. From this perspective, the design of a didactic-methodological proposal based on the teaching-learning process of body orientation in the football development stage was presented, to contribute to the organized attack. Methodologically, it is a projective research, with a qualitative approach, with a documentary design of an evolutionary temporality, using the data review technique, to categorize, collect, organize and analyze the information obtained. In a matrix of analysis, categories and registration, the execution of all the analytical, comparative, explanatory and projective stages was carried out, presenting in each one the methodology and the results obtained. The population corresponds to 16 men between the ages of 12 and 13 belonging to the sub 13 category of Club Deportivo La Gaitana, participants in the Bogotá Soccer League, Premier Division. It is intended to enhance the offensive game of the teams based on the didactic and methodological guidelines developed in the proposal.
Keywords: body orientation; didactic-methodological proposal; organized attack; soccer; teaching-learning process